Gifted students: Analysis among psychological problems, social, and emotional well-being - Suyitno, Suyitno; Winarto; Sulistiana, Devita; Supriyono (Edelweiss Applied Science and Technology, 2024)
Gifted and talented learners experienced life’s storms and stresses just like their peers. However, because of their unique characteristics, they also dealt with some psychological issues such as anxiety, stress, and depression, which are closely related to their gifted characteristics. This research aims to examine: (a) psychological problems, (b) psycho-social and emotional well-being, and (c) the connection between gifted and talented students’ wellbeing and psychological issues. This research design uses descriptive quantitative methods. A series of questions (DASS) were used to gather data from 112 gifted students, who were involved in this research and identified as gifted students. Next, the DASS and Social Well-Being questionnaires were collected and compared, to determine psychological problems and social well-being among gifted students. Descriptive (mean) and inferential analyzes were carried out on quantitative data. Analysis shows that there are psychological problems in gifted students at school, namely depression, stress and anxiety. The findings indicate that stress is one of the most prevalent issues (mean=33.8), followed by anxiety (mean=33.2) and depression (mean=24.9). Apart from that, the research results also show a negative correlation between psychological problems and well-being.